The Impact of Combined Cranberry Supplementation and Weight Loss Diet on Inflammatory, Antioxidant, and Apoptosis Biomarkers in Patients with Non-Alcoholic Fatty Liver Disease: A Randomized, Double-Blinded, Controlled Clinical Trial - Razie Hormoznejad; Majid Mohammad Shahi; Sepideh Mahboobi; Fakher Rahim; Bijan Helli; Pezhman Alavinejad; Narges Dehghanseresht; Narges Sadeghi; Asaad Sharhani (Journal of Nutrition and Food Security)
Non-alcoholic fatty liver disease (NAFLD) is a prevalent chronic liver disease. The aim of this study is to evaluate the effect of combined weight loss diet and cranberry supplementation on anthropometric measurements, inflammation and antioxidant biomarkers in patients with NAFLD. Methods: In this randomized, double-blinded, and controlled clinical trial, 41 NAFLD patients were supplemented with either cranberry or placebo tablets for 12 weeks. Both groups followed a diet of 500-1000 calories less than the estimated energy requirements. Serum levels of total antioxidant capacity (TAC), malondialdehyde (MDA), cytokeratin 18 M30 (CK-18 M30), chemokine C-C motif ligand 2 (CCL2) and tumor necrosis factor alpha (TNF-α) were measured at both baseline and the end of the study. Results: Significant improvements in TAC were observed in the cranberry group and between the two groups (P=0.006 and P=0.011, respectively), but the changes in the placebo group were not significant (P=0.325). There were no statistically significant differences in the serum levels of MDA, CK-18 M30, CCL2 and TNF-α between the cranberry and the placebo groups (P>0.05).  Conclusions: It seems that daily consumption of cranberry supplement would be beneficial in increasing serum levels of TAC. Further studies are needed to investigate the effects of anti-inflammatory and antioxidant properties of cranberry on NAFLD.